Thromboembolic and atherosclerotic cardiovascular events in inflammatory bowel disease: epidemiology, pathogenesis and clinical management - Sleutjes, Jasmijn A. M. (Therap Adv Gastroenterol, 2021)
Inflammatory bowel disease (IBD) is associated with an increased risk of cardiovascular disease (CVD). The increased risk of CVD concerns an increased risk of venous thromboembolism (VTE), atherosclerotic cardiovascular disease (ASCVD) and heart failure (HF), at corresponding relative risks of 2.5, 1.2 and 2.0, respectively, as compared with the general population. Especially young patients under the age of 40 years run a relatively high risk of these complications when compared with the general population. Chronic systemic inflammation causes a hypercoagulable state leading to the prothrombotic tendency characteristic of VTE, and accelerates all stages involved during atherogenesis in ASCVD. Increased awareness of VTE risk is warranted in patients with extensive colonic disease in both ulcerative colitis and Crohn’s disease, as well as during hospitalization, especially when patients are scheduled for surgery. Similarly, critical periods for ASCVD events are the 3 months prior to and 3 months after an IBD-related hospital admission. The increased ASCVD risk is not fully explained by an increased prevalence of traditional risk factors and includes pro-atherogenc lipid profiles with high levels of small dense low-density lipoprotein cholesterol particles and dysfunctional high-density lipoprotein cholesterol. Risk factors associated with HF are location and extent of inflammation, female sex, and age exceeding 40 years. A dose-dependent increase of overall CVD risk has been reported for corticosteroids. Immunomodulating maintenance therapy might reduce CVD risk in IBD, not only by a direct reduction of chronic systemic inflammation but possibly also by a direct effect of IBD medication on platelet aggregation, endothelial function and lipid and glucose metabolism. More data are needed to define these effects accurately. Despite accumulating evidence on the increased CVD risk in IBD, congruent recommendations to develop preventive strategies are lacking. This literature review provides an overview of current knowledge and identifies gaps in evidence regarding CVD risk in IBD, by discussing epidemiology, pathogenesis, and clinical management.